Optimalization of NaOH concentration in alkaline lysis method on quality and quantity of Candida albicans DNA - Putri, Nasya Desinta; Prayekti , Endah (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2025)
Background: Candida albicans was a major caused of invasive candidiasis whose discovery by culture took a longed timed. Polymerase Chain Reaction (PCR) was a deoxyribonucleicacid (DNA)-based rapid diagnostic method. The simple DNA isolation method of alkaline lysis needed to optimized for Candida albicans, which had a complex cell wall that is difficult to broke. The concentration of NaOH in the alkaline lysis method is one of the things that affects the results of DNA isolation. Objective: The purpose of this studied was to determine the effect of optimizing the concentration of NaOH in the alkaline lysis method on the quality and quantity of Candida albicans DNA. Materials and Methods: This researched is experimental by performed DNA isolation used alkaline lysis method used NaOH concentrations of 1.5 N, 1.75 N, and 2.0 N and controlled (NaOH 0.2 N). Calculation of DNA quality and quantity using a nanodrop spectrophotometer. Results: The results showed the ordered of obtained the high to low DNA quality (A260/280) was NaOH concentration 2.0 N>1.75 N>1.5 N>0.2 N (1.86±0.44-0.95±0.18) while for DNA quantity was NaOH concentration 2.0 N>1.75 N>1.5 N>0.2 N (187.7±58.3-9.6±3.5 ng/ml). Conclusion: There is an effect of optimizing NaOH concentration on the lysis of fungal cell walls in the alkaline lysis method, namely increased the purity valued and concentration of sample DNA isolation results gradually. The use of 2.0 N NaOH concentration produced the best quality and quantity of DNA, namely 1.86±0.44 for DNA quality and 187.7±58.3 for DNA quantity.